2021
DOI: 10.1021/acsaem.1c01641
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cycle Life through Fast Formation Using a Superconcentrated Phosphonium Based Ionic Liquid Electrolyte for Anode-Free and Lithium Metal Batteries

Abstract: Cell formation of lithium-ion cells impacts the evolution of the solid electrolyte interphase (SEI) and the cell cycle stability. Lithium metal anodes are an important step in the development of high energy density batteries owing to the high theoretical specific capacity of lithium metal. However, most lithium metal battery research has used a conventional lithium-ion formation protocol; this is time-consuming and costly and does not account for the different properties of the lithium metal electrode. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…However, a high negative surface charge of −14.4 μC/cm 2 significantly stabilizes Li + and also decreases the FSI content, making the Li x FSI y ( x > y ) aggregates positively charged as a whole, and [C3mpyr] + and DME tend to be pushed away toward the bulk phase. This IL cation-to-Li x FSI y ( x > y ) aggregate replacement at high negative electrode polarization was previously seen for other superconcentrated IL electrolytes, which explains the increase of inorganic SEI components upon high current density preconditioning. , Moreover, we have also found that IL cation chemistry (e.g., phosphonium vs pyrrolidinium) may affect this process, making this replacement easier in an electrolyte with the weaker IL cation–surface and IL cation–other ions interactions, such as those ILs containing small phosphonium [P 1222 ] + (Figures S9 and S11–S13), as shown in the previous work . The detailed coordination analysis of lithium is discussed next.…”
Section: Molecular Understanding Of the Edl And Its Relationship To E...supporting
confidence: 74%
See 1 more Smart Citation
“…However, a high negative surface charge of −14.4 μC/cm 2 significantly stabilizes Li + and also decreases the FSI content, making the Li x FSI y ( x > y ) aggregates positively charged as a whole, and [C3mpyr] + and DME tend to be pushed away toward the bulk phase. This IL cation-to-Li x FSI y ( x > y ) aggregate replacement at high negative electrode polarization was previously seen for other superconcentrated IL electrolytes, which explains the increase of inorganic SEI components upon high current density preconditioning. , Moreover, we have also found that IL cation chemistry (e.g., phosphonium vs pyrrolidinium) may affect this process, making this replacement easier in an electrolyte with the weaker IL cation–surface and IL cation–other ions interactions, such as those ILs containing small phosphonium [P 1222 ] + (Figures S9 and S11–S13), as shown in the previous work . The detailed coordination analysis of lithium is discussed next.…”
Section: Molecular Understanding Of the Edl And Its Relationship To E...supporting
confidence: 74%
“…8,45 Moreover, we have also found that IL cation chemistry (e.g., phosphonium vs pyrrolidinium) may affect this process, making this replacement easier in an electrolyte with the weaker IL cation−surface and IL cation− other ions interactions, such as those ILs containing small phosphonium [P 1222 ] + (Figures S9 and S11−S13), as shown in the previous work. 45 The detailed coordination analysis of lithium is discussed next.…”
Section: Its Relationship To Electrochemical Performancesupporting
confidence: 67%
“…The electrode potential varies in a working battery, so it is also worthwhile to explore the sensitivity of interfacial structures to the electrode potential. ,, As mentioned previously, the CPMs model the electrode potential, electrode polarization, and charge distribution more reasonably than FCMs because the charge fluctuation of the electrode caused by the electrolyte is considered in CPMs. The CPM was first developed by Reed et al and further revised by Gingrich and Wilson. ,, In this method, electrode atoms carry a Gaussian charge distribution and the derivative of the electrostatic energy of the system with respect to electrode charges leads to the applied potential.…”
Section: Electrolyte Microstructuresmentioning
confidence: 99%
“…The mass of electrolyte was not included in the calculation to allow the comparison with literature reports. 27,40 The stack specific energy was determined to be 480 W h kg À1 and the energy density was 798 W h L À1 . The cell parameters are tabulated in Table S2 (ESI †).…”
Section: Papermentioning
confidence: 99%